Unraveling Obamacare—Can Congress and the Supreme Court Undo Health Care Reform?. Issue 4 (April 2015) - Oberlander, Jonathan
<x xml:space="preserve">Abstract</x> ABSTRACT The elections in 2014 gave control of Congress and several governorships to the Republicans, all of which could have long-ranging ramifications for the Affordable Care Act (ACA). Republicans will renew efforts to repeal Obamacare, but without the supermajority in the Senate, the process may be difficult. Moreover, budget reconciliation cannot be used to negate the entire ACA, and even if successful, President Obama would veto any legislation. Another option is to use a targeted approach to overturn specific provisions of the ACA, including the mandates that individuals obtain health insurance or pay a penalty and that larger employers offer health coverage to workers or pay a penalty. A tax on medical devices and weakening or eliminating the Independent Payment Advisory Board are other possibilities. These provisions are vulnerable because of their unpopularity with the public, opposition from interest groups, and lack of strong congressional support from both parties. Although the president might accept limited changes, he will not allow substantial revisions that threaten the ACA's viability. As long as Obama is in office, congressional repeal of the ACA remains unlikely. But whether Republicans could overturn Obamacare after Obama's presidency ends is still a possibility because the ACA was politically shaky from the start. It has never had strong public support, it was not bipartisan, and it passed through Congress without any votes from Republicans. Its diverse policies, regulations, and subsidies limited its identity. Governors and legislatures opposed to Obamacare have slowed its progress within their states. Implementation of the law's major provisions expanding insurance coverage did not begin until more than 3 years after its passage, time during which opponents mounted challenges before the ACA's benefits were available. The ACA's benefits are now a reality, despite the dreadful opening implementation process. Almost 7 million people are covered through health insurance marketplaces, with millions more expected to join in the future. Enrollment in Medicaid and the Children's Health Insurance Program increased by nearly 9 million this past year because 28 states expanded Medicaid. The uninsured population has decreased by about 10 million persons since 2013. The health care industry is benefitting from increased service use by newly insured patients and is creating ACA payment and delivery system reforms. Although the ACA has many problems, its ongoing implementation and success constrain any efforts to repeal the law. With each year, it expands and becomes a larger part of American life. It has forever changed health policies, and although changes could be made, it likely will not be eliminated from the health care system. Currently, there is a case before the Supreme Court that questions the legality of subsidies for health insurance for individuals utilizing the federal health insurance exchanges. Depending on how the Court rules, the question is whether Obamacare will remain intact. If the Court narrows the ACA's scope, the law's recent momentum will change, the fight will escalate, and the future of health care reform will be uncertain.